Adjusting Frequency of Pump Blade Angles and Optimal Operation for Large Pumping Station System. (28th November 2013) - Feng, Xiaoli; Qiu, Baoyun
Abstract : For pumping stations installed blade full-adjustable pumps with frequently varying head in a wide range, adjusting pump blade angles is an effective way to realize optimum operation. Optimal mathematical models were established aiming at the least daily operation cost for pumping station system, which includes main pump units, inlet and outlet passages and their accessories, forebay and outlet pond, auxiliary equipment, power transmission and transformation equipment, other electromechanical equipments and lightings. Also, head varying, time-varying electrical price, and blade adjusting frequency are all taken into account. Meanwhile, the influences of the blade adjusting frequency on operation cost are researched. The results indicate that the operation cost is reduced by 5.64% ~ 12.13% by the optimal schemes considering time-varying electrical price and adjusting pump blade angles than that of conventional schemes, taking Jiangdu Forth Pumping Station in China as a case. The more the blade adjusting frequency, the less the operation cost. Also, if the blade adjusting frequency exceeds eight times, the optimum operation cost is close to be a const. Therefore, it is advisable to adjust blade angles four to six times a day to save operation cost and guarantee the reliability of pump units.